Microhardness of glass carbomer and high-viscous glass Ionomer cement in different thickness and thermo-light curing durations after thermocycling aging - Mehmet Buldur; Emine Sirin Karaarslan (BMC, 2019)
Abstract Background The objective of our study was to compare the upper and lower surface microhardness and surface changes of Glass Carbomer Cement (GCP) and EQUIA Forte (EF) in different thickness after thermo-light curing durations and aging. Methods A total of 504 samples (5 mm-diameter) were prepared by using GCP-252 (GCP Dental, and Vianen, Netherlands) and EF-252 (EQUIA Forte, GC, Tokyo, Japan). Three different thickness samples (2, 4, and 6 mm) were prepared with 84 samples in each subgroup. The samples were prepared by three curing procedures (Non-exposed, 60s, 90s). Their varnishes were applied to the upper surfaces of half of each subgroup (n = 7). The upper microhardness measurements were evaluated before and after aging. To compare the effect of different thicknesses, the bottom surfaces of the samples were evaluated before aging in terms of microhardness measurements. Also, the upper surfaces were analyzed in the SEM before and after aging. Results The upper surface values of all the samples were higher than the bottom values (p < 0.05). There were no significant differences between the varnished and non-varnished samples in both materials (p > 0.05). Although this increase was not significant in some groups, temperature variations increased the surface microhardness values of both materials except for the non-exposed-varnished EF samples. The highest microhardnesses values were recorded in the non-exposed-varnished EF (125.6 ± 6.79) and unvarnished GCP (88.1 ± 7.59) samples which were thermo-light cured for 90 s before aging. The bottom hardness values were affected by thickness variations in both GCP and EF materials (p < 0.05). The sample deformations and microcracks after aging were greater than before in all the materials. Thermo-light curing in 90 s to the samples reduced the cracks in both the materials before and after aging. Conclusions Thermal aging adversely affected the microhardness of the materials, which is important for clinical success. The thermo-light curing process improved the microhardness of the GCP group without varnish application. Varnish application increased the microhardness of the EF group without applying thermo-light curing. The microhardness of the bottom surfaces decreased with increasing thickness. The thermo-light curing did not increase the bottom surface microhardness of all the samples.